An architecture for a viable information system : application of “viable system model” in modern systems architecture for the creation of viable information system - Buhryk, Anton Selin (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management